Is the effect of person-organisation fit on turnover intention mediated by job satisfaction? A survey of community health workers in China. Issue 2 (22nd February 2017) - Zhang, Mingji; Yan, Fei; Wang, Wei; Li, Guohong
Abstract : Objectives: Person-organisation fit (P-O fit) is a predictor of work attitude. However, in the area of human resource for health, the literature of P-O fit is quite limited. It is unclear whether P-O fit directly or indirectly affects turnover intention. This study aims to examine the mediation effect of job satisfaction on the relationship between P-O fit and turnover intention based on data from China. Design and methods: This is a cross-sectional survey of community health workers (CHWs) in China in 2013. A questionnaire of P-O fit, job satisfaction and turnover intention was developed, and its validity and reliability were assessed. Multiple regression and structural equation modelling were used to examine the relationship among P-O fit, job satisfaction and turnover intention. Setting and participants: Multistage sampling was applied. In total, 656 valid questionnaire responses were collected from CHWs in four provincial regions in China, namely Shanghai, Shaanxi, Shandong and Anhui. Results: P-O fit was directly related to job satisfaction (standardised β 0.246) and inversely related to turnover intention (standardised β −0.186). In the mediation model, the total effect of P-O fit on turnover intention was −0.186 (p<0.001); the direct effect of P-O fit on turnover intention was −0.094 (p<0.01); the indirect effect of job satisfaction on the relationship between P-O fit and turnover intention was −0.092 (p<0.001). Conclusions: The effect of P-O fit on turnover intention was partially mediated through job satisfaction. It is suggested that more work attitude variables and different dimensions of P-O fit be taken into account to examine the complete mechanism of person-organisation interaction. Indirect measures of P-O fit should be encouraged in practice to enhance work attitudes of health workers.